Business informality in Colombia: an obstacle for creative destruction (2010)
This document studies the effects of business informality in terms of distortions in resource absorption, particularly labor, by informal companies. It also assesses the consequences of lower demand for labor of informal firms over aggregate productivity. With firm level data from the DANE Micro-establishments Survey, a matching exercise between formal and informal firms is conducted. It was found that the latter hire fewer employees than formal firms with the same characteristics, including Total Factor Productivity. The matching results allow using counterfactual demands of labor of informal firms to calculate and compare the real and counterfactual aggregate productivity levels. The results indicate that if informal firms would demand the amount of employment demanded by similar formal firms, market share distribution of firms would improve and this would positively affect aggregate productivity.